Breaking the silence - Montinola, Lourdes R. (Quezon City University of the Philippines Press and the Creative Writing Center, 1996)
Author's account on Japanese atrocities during the liberation of Manila.
"To commemorate the centennial year of Dr. Reyes's birth"--Back cover.
Keywords: Philippines -- History -- Japanese occupation, 1942-1945 -- Personal narratives